The Efforts of the Intelligence and Security Unit in Early Detection of Disclosure of Illicit Trafficking of Methamphetamine in the Balikpapan Police Area - Ekky Putra (Police Studies Review, 2021)
This research was motivated by the increasing illicit trafficking of methamphetamine drugs in Balikpapan which was successfully uncovered in 2020, an increase of 10 (ten) times compared to the previous year. Therefore, in uncovering the drug crime, the Balikpapan Police Intelligence and Security Unit seeks to optimize early detection of intelligence so that its implementation is in accordance with Perkabaintelkam No. 1 of 2013 concerning Police Intelligence Investigations. This study aims to: (1) describe the efforts of the Balikpapan Police Intelligence and Security Unit in early detection of the illicit trafficking of methamphetamine, (2) explain the factors that influence the early detection of the illicit trafficking of methamphetamine. In the conceptual literature the author uses various concepts to analyze the problems above. The concepts as the theoretical basis are: the concept of intelligence, the concept of police operational management, the concept of early detection, the concept of basic intelligence, the concept of illicit drug trafficking, and the concept of proactive policing. This study used a qualitative approach with Field Research Methods, primary and secondary data sources, and used data triangulation to obtain data validity. The results of the study indicate that the implementation of early detection by the intelligence unit to uncover the illicit trafficking of methamphetamine in the Balikpapan Police jurisdiction is not optimal because the implementation of tasks in the field is not balanced with the number of human resources needed to focus on priority targets that occur or there is no renewal of infrastructure facilities. owned. The conclusions in this thesis, (1) The implementation of early detection in closed intelligence investigations is still not optimal, and (2) influencing factors such as human, material and logistical resources have not been well supported. Suggestions in this thesis, the addition of personnel is very necessary because the number of personnel is still far from the list of personnel composition that should be. Then, in carrying out investigations other than in updating alsus intelligence, in making products for carrying out tasks, you can use a renewable application system as a forum for collecting intelligence products for leaders.